Nail Psoriasis in a Child Observed Under Ultraviolet Dermoscopy Treated by a Topical Biological Agent Cream: A Case Report - Run-Yan Gao; Sushmita Pradhan; Yu-Ping Ran (Wolters Kluwer Health, 2021)
Abstract. Introduction:. Nail psoriasis is a type of psoriasis involving nail lesions characterized by pitting, onycholysis, longitudinal ridges, and subungual hyperkeratosis. We herein describe a 9-year-old girl with nail psoriasis who presented with nail crumbling and was treated with topical cream containing 45 μg/g mouse monoclonal antibody to human interleukin -8. Case presentation:. A 9-year-old Chinese girl presented with a 6-month history of a rough, thickened fingernail and toenails. Nail plate crumbling, onycholysis, and fissured periungual folds were observed under dermoscopy and ultraviolet dermoscopy. The nails were soaked in warm water, then topical wrapped with Abcream cream overnight. After about 4 months of treatment, the nails significantly improved by both dermoscopy and ultraviolet-dermoscopy evaluattion. Discussion:. Due to the different wavelengths of light emitted by polarized light dermatoscope and ultraviolet-dermatoscope, the characteristics of observation will be different. Abcream acts by antagonizing human interleukin -8, inhibiting leukocyte chemotaxis and neovascularization, and regulating the abnormal proliferation and differentiation of keratinocytes. Conclusion:. Ultraviolet-dermoscopy is pivotal in evaluating the severity and potency of nail psoriasis. And Abcream can be regarded as a new drug for the treatment of nail psoriasis in children.